EVOLUTION AND DEVELOPMENT TRENDS OF INTERNATIONAL BUSINESS UNDER GLOBALIZATION (Marketing Journal, 2025)
The article examines certain aspects of the emergence and development of international business and its impact on the formation of the global economy and integration processes. Special attention is given to the historical stages of international economic r elations as well as current challenges related to globalization, competition, and digitalization.
Keywords: international business; history; global economy; globalization; integration; digitalization; development challenges